Bridging the Great Divide between State and Society (A Study on Two Initiatives of Enhancing the State ?Society Synergy in Sri Lanka) - Jayathilaka, Aruna; Purasinghe, P. L. T. (Asian Development Policy Review, 2017)
A ‘great divide’ exists between the society and the state, due the mistrust and lack of confidence from citizens towards state authorities or public administration. The hostility between state and society creates a “vicious circle” which brings great harm for both state and civil society. The importance of bridging the gap between state and society has being emphasized by many scholars, for achieving economic development and enjoying the maximum benefit of democracy. Positive-sum interaction between state and society should be developed for turning the above mentioned “vicious circle” into a “virtuous circle”. This paper critically examines two main attempts in Sri Lanka which aimed to bridge the above mentioned gap.